Meningkatkan Keterampilan Passing Bawah Bolavoli Menggunakan Permainan 4 On 4 Peserta didik: Refleksi Hasil Belajar di Kelas IX A SMP Negeri 3 Rogojampi Kabupaten Banyuwangi - Jumadi, Jumadi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
The inadequate passing capabilities of Ball Voli kids in class IX A at Pangsid Pangsid Public Middle School in Sidenreng Rappang prompted this investigation. The goal of this study is to see if playing a four-on-four game may help pupils improve their passing skills. This study is a collaborative and interactive classroom action research project. It is divided into two cycles, each of which includes planning, implementation, and observation, as well as reflection. A total of 29 pupils from class IX A were included in the study. Tests are used in data collecting strategies. Data analysis procedures are descriptively qualitative and quantitatively carried out. The results revealed that students' passing abilities improved when they played volleyball in a four-on-four format. For example, according to the findings of the cycle I evaluated, 10 students (32.26 percent) finished their learning, while 19  students (67.74 percent) had not yet done it. The results of the cycle II examination revealed that 29 pupils (93.55 percent) had finished their learning, while 2 students (6.45 percent) had not. Keywords: passing down, game 4 on 4. According to the average findings obtained, the second cycle of the cycle I saw a 20.18 percent gain. As a result, it can be inferred that using 4 on 4 games can improve a student volleyball player's passing abilities.